Pengaruh Strategi Pemasaran dan Packaging terhadap Keputusan Pembelian Pancake Ucok Durian - Aryani Sairun; Sugito Sugito (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The culinary product market, particularly Pancake Ucok Durian in Medan City, demands effective marketing strategies and attractive packaging designs to enhance consumer purchasing decisions. This study aims to analyze the influence of marketing strategies and packaging designs on consumer purchase decisions. A quantitative survey using purposive sampling was conducted on 200 active consumers within the last six months. Data were collected through structured questionnaires and analyzed using multiple regression. The results show that marketing strategies have a positive and significant effect on purchase decisions, contributing 41.2%. Meanwhile, packaging design has a more dominant influence, contributing 43.4%. Simultaneously, both variables explain 55.1% of the variation in consumer purchase decisions. These findings highlight the importance of optimizing marketing strategies and packaging design to strengthen Pancake Ucok Durian’s competitiveness in the market